Study on Mutual Fund Good Investment Avenue for Common People in India: Addressing the Diverse Investment Needs of Individual Investors (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Mutual funds in India now provide a wide range of specialised schemes, or investmentoptions, to meet the needs of a broad spectrum of investors with varying risk tolerances and returnexpectations. Lack of financial knowledge and a lack of time to research investment alternatives are two ofthe most common reasons. Moreover, certain financial markets have a high barrier to entry, making itdifficult for a low-volume investor to take part in the market's expansion. Not all investors have the samerequirements from their investments. Some investors may be content with money preservation, whileothers will always be on the lookout for profitable opportunities. Others may want a more constant rateof return on their investments, while others aim to put money away for things like retirement or theirchildren's college tuition. Investors have a wide range of needs and goals, making it impossible for asingle financial product to meet all of them. Mutual funds have been more popular over the last decadebecause they can accommodate many different types of participants via their many different investmentstrategies.